A Design of SMS (Short Massage Service) Based Horticultural Information System for Sub Agribusiness Terminal Mantung, Malang - Dewi, Ika Atsari; Sucipto, Sucipto; Mulyarto, Aunur Rofiq (Fakultas Teknologi Pertanian Universitas Brawijaya, 2006)
The objective of this research was to set up the SMS based agricultural commodities information system that run well and provide accurate and speedy information at a reasonably low cost, particularly for horticultural products marketed at Sub Agribusiness Terminal (STA) Mantung Agribis Center in Malang Regency. The Agribusiness information outputs consist of suppliers, sale transactions, buyers, purchasing transactions, and commodities information. The required data were Government, Suppliers, and Buyers. The system users would be Suppliers, buyers, Managers of Agribusiness Terminals, Sub Agribusiness Terminal and main markets, and related government and private bodies. A descriptive-analytical method, so-called the prototyping approach, was chosen. The research was started in two main stages, first, an identification of usersâ€™ needs and a development of a system prototype that covered the conceptual design, architecture design, and program implementation (coding). The architecture of the design consisted of data base, process, user interface, and network design. The software employed were Gammu, Firebird 1.5, SMS Demon and Delphi 7.0. The hardware required include the Auto Respond SMS application, a compute set equipped with a GSM modem, and a GSM network. The information in the developed system, however, was not real time since the data was first collected from the sources, then the collected data was input and processed. Therefore, there will be a time delay, depending on the time to execute this sequence. The results indicated that the developed system was able to provide users the relevance information within 15-30 seconds at a cost of not more than regular SMS charge. Â Key words: SMS-based horticultural information system